Regulation of PIK3C3/VPS34 complexes by MTOR in nutrient stress-induced autophagy - Yuan, Hai-Xin (Landes Bioscience, 2013)
Autophagy is a cellular defense response to stress conditions, such as nutrient starvation. The type III phosphatidylinositol (PtdIns) 3-kinase, whose catalytic subunit is PIK3C3/VPS34, plays a critical role in intracellular membrane trafficking and autophagy induction. PIK3C3 forms multiple complexes and the ATG14-containing PIK3C3 is specifically involved in autophagy induction. Mechanistic target of rapamycin (MTOR) complex 1, MTORC1, is a key cellular nutrient sensor and integrator to stimulate anabolism and inhibit catabolism. Inactivation of TORC1 by nutrient starvation plays a critical role in autophagy induction. In this report we demonstrated that MTORC1 inactivation is critical for the activation of the autophagy-specific (ATG14-containing) PIK3C3 kinase, whereas it has no effect on ATG14-free PIK3C3 complexes. MTORC1 inhibits the PtdIns 3-kinase activity of ATG14-containing PIK3C3 by phosphorylating ATG14, which is required for PIK3C3 inhibition by MTORC1 both in vitro and in vivo. Our data suggest a mechanistic link between amino acid starvation and autophagy induction via the direct activation of the autophagy-specific PIK3C3 kinase.